Effect of post isometric relaxation technique in mechanical neck pain: a case study - S., Haripriya; Krishna, Harish S.; R. B., Apeksha (International Journal of Research in Medical Sciences, 2024)
Neck pain is one of the most common musculoskeletal disorders among the population. The purpose of the study was to investigate the effect of muscle energy technique in the form of post isometric relaxation technique (PIR) on pain and range of motion in a patient with chronic mechanical neck pain (MNP). A 35-year-old woman with MNP was treated with PIR for 3 weeks. Neck pain and disability was measured using neck disability index scale (NDI) and numerical pain rating scale while ROM of cervical spine was measured with universal goniometer. The patient has significant decrease in pain and significant improvement in range of motion and functional disability using NDI showed improvement from moderate disability to mild disability. Post isometric relaxation technique is effective in reducing pain and functional disability and increasing cervical range of motion in mechanical neck pain.